آليات مكافحة الفساد وفق التعديل الدستوري لسنة 2020 - فاطمة الزهرة حكيم (My University, 2023)
Abstract : Corruption is a dangerous and destructive phenomenon, because of its negative effects on the economies of many countries. It constitutes a crime that threatens social, food, economic, political, legal and judicial security in all its dimensions, and there is no way to eliminate this crime and besiege it except through effective oversight mechanisms to combat corruption, including the Court of Auditors, Which is one of the most important supervisory institutions that the legislator has given importance, and the second supervisory mechanism is civil society institutions, which also have an important role to reduce corruption But through the cooperation of all bodies, institutions and individuals, the third and last supervisory mechanism to address corruption crimes is the Supreme Transparency Authority for the Prevention and Combating of Corruption, which came in accordance with the constitutional amendment of 2020 and regulated by Law No. 22-08. ................................. ملخص المذكرة: يعتبر الفساد ظاهرة خطيرة ومدمرة، لما لها من آثار سلبية على اقتصاديات كثير من الدول، ذلك أنها تشكل جريمة تهدد الأمن الاجتماعي والغذائي والاقتصادي والسياسي والقانوني والقضائي بكافة أبعاده، ولا سبيل للقضاء على هذه الجريمة ومحاصرتها الا عن طريق آليات رقابية فاعلة لمكافحة الفساد منها مجلس المحاسبة، الذي يعد من أهم المؤسسات الرقابية التي أولاها المشرع أهمية، وثاني آلية رقابية هي مؤسسات المجتمع المدني التي هي أيضا لها دور هام للحد من الفساد، ولكن عن طريق تعاون كافة الهيئات والمؤسسات والأفراد، وثالثا وآخر آلية رقابية لتصدي لجرائم الفساد هي السلطة العليا للشفافية للوقاية من الفساد ومكافحته، التي جاءت وفق التعديل الدستوري لعام 2020 ونظمها القانون رقم22-08 ............................. résumé : La corruption est considérée comme un phénomène dangereux et destructeur, en raison de ses effets négatifs sur les économies de nombreux pays, car elle constitue un crime qui menace la sécurité sociale, alimentaire, Économique, Politique, Juridique et judiciaire dans toutes ses dimensions, et il n'y a aucun moyen d'éliminer ce crime et de l'assiéger uniquement par des mécanismes de contrôle efficaces pour lutter contre la corruption, y compris le Conseil comptable, qui est l'un des plus importants la corruption est l'autorité suprême de transparence pour la prévention et la lutte contre la corruption, qui est venue Conformément à l'amendement constitutionnel de 2020 et réglementé par la loi n ° 22-08.